(Un)common knowledge: Children use social relationships to determine who knows what. Issue 6 (20th April 2020) - Liberman, Zoe; Gerdin, Emily; Kinzler, Katherine D.; Shaw, Alex
Abstract: Socially savvy individuals track what they know and what other people likely know, and they use this information to navigate the social world. We examine whether children expect people to have shared knowledge based on their social relationships (e.g., expecting friends to know each other's secrets, expecting members of the same cultural group to share cultural knowledge) and we compare children's reasoning about shared knowledge to their reasoning about common knowledge (e.g., the wrongness of moral violations). In three studies, we told 4‐ to 9‐year‐olds ( N  = 227) about what a child knew and asked who else knew the information: The child's friend (Studies 1–3), the child's schoolmate (Study 1), another child from the same national group (Study 2), or the child's sibling (Study 3). In all three studies, older children reliably used relationships to infer what other people knew. Moreover, with age, children increasingly considered both the type of knowledge and an individual's social relationships when reporting who knew what. The results provide support for a 'Selective Inferences' hypothesis and suggest that children's early attention to social relationships facilitates an understanding of how knowledge transfers – an otherwise challenging cognitive process. Abstract : Tracking people's knowledge can be challenging for children. We find evidence that children use social relationships when making inferences about knowledge. Specifically, children expect friends to have shared personal knowledge (e.g., secrets), and expect siblings and members of a national group to have shared cultural knowledge (e.g., how to celebrate a holiday). Moreover, with age, children become increasingly likely to consider both the type of relationship and the type of knowledge when determining who knows what.